2018
DOI: 10.1007/s10863-018-9753-0
|View full text |Cite
|
Sign up to set email alerts
|

Alternative mitochondrial respiratory chains from two crustaceans: Artemia franciscana nauplii and the white shrimp, Litopenaeus vannamei

Abstract: Mitochondrial ATP is synthesized by coupling between the electron transport chain and complex V. In contrast, physiological uncoupling of these processes allows mitochondria to consume oxygen at high rates without ATP synthesis. Such uncoupling mechanisms prevent reactive oxygen species overproduction. One of these mechanisms are the alternative redox enzymes from the mitochondrial respiratory chain, which may help cells to maintain homeostasis under stress independently of ATP synthesis. To date, no reports h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…We have shown that AOX is in the genomes of multiple species of copepods from around the world that inhabit a wide variety of ecological niches (Table 2.) The first reports of AOX from arthropods were in the brine shrimp Artemia franciscana and putative sequences from other members of the Chelicerata, Hexapoda, and Crustacea (Rodriguez-Armenta et al, 2018;McDonald and Gospodaryov, 2018). It was previously hypothesized that AOX was not present in arthropods due to a gene loss event (McDonald et al, 2009), however, the above data refute this hypothesis.…”
Section: Discovery Of Aox In Copepods and The Phylum Arthropodamentioning
confidence: 93%
See 2 more Smart Citations
“…We have shown that AOX is in the genomes of multiple species of copepods from around the world that inhabit a wide variety of ecological niches (Table 2.) The first reports of AOX from arthropods were in the brine shrimp Artemia franciscana and putative sequences from other members of the Chelicerata, Hexapoda, and Crustacea (Rodriguez-Armenta et al, 2018;McDonald and Gospodaryov, 2018). It was previously hypothesized that AOX was not present in arthropods due to a gene loss event (McDonald et al, 2009), however, the above data refute this hypothesis.…”
Section: Discovery Of Aox In Copepods and The Phylum Arthropodamentioning
confidence: 93%
“…Heterologously expressed AOX proteins from Ciona intestinalis and Crassostrea gigas are 35-42 kDa in size (Hakkaart et al, 2006;Robertson et al, 2016). The AOX protein of Artemia franciscana is between 25 and 37 kDa on Western blots using the anti-AOX Sauromatum guttatum monoclonal antibody (Rodriguez-Armenta et al, 2018). It is expected that the food source (Spirulina) would contain AOX as it is an algae, however, the AOX antibody did not recognize a protein in this sample (Figure A.3).…”
Section: Discovery Of Aox In Copepods and The Phylum Arthropodamentioning
confidence: 94%
See 1 more Smart Citation
“…In the case of C. gigas, AOX contribution to the oyster adjustments to short-term hypoxia and re-oxygenation was considered in isolated mitochondria [17] but the presented data do not allow for clear conclusions as the observed AA-resistant respiration was not shown to be eliminated by AOX inhibitor, for example by benzohydroxamic acid (BHAM) [35]. Moreover, to observe the enzyme activity in the shrimp isolated mitochondria the authors applied an uncoupler to increase the recorded oxygen uptake rate [32].…”
mentioning
confidence: 99%
“…The second one was heterologously expressed in mitochondria of cultured human cells [9,[20][21] as well as in the fruit y Drosophila (Sophophora) melanogaster [22] [23][24][25][26][27] and mouse [9,12,[28][29]. Additionally, some experimental data concerning AOX protein are available for crustaceans, the brine shrimp Artemia franciscana [30], the white shrimp Litopenaeus vannamei [31] [32] and the marine copepod Tigriopus californicus [33] [34]. In the case of both the shrimps the data concerns AOX activity in isolated mitochondria whereas in the case of the copepod amounts of AOX mRNA and protein in various life stages of the animal and under stress temperature conditions were studied.…”
mentioning
confidence: 99%